PUBLIC COMPLIANCE: A NECESSITY FOR BRAZIL (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2024)
The scope of this work is to address the impacts of implementing Compliance in the public sector, as a tool to combat corruption and consolidate collective rights, advance the economy and increase a positive reputation. Thus, the institute, when implemented by legal entities governed by public law and state-owned companies, is called, by doctrine, as Public Compliance. In addition, it has been promoted in various international and national legislations, such as the United Nations Convention on Corruption, adopted by the General Assembly on October 31, 2003, and the State-Owned Companies Law (Law No. 2016). Another important point is the concomitant use of corporate governance to achieve public integrity, through its principles of equity, transparency, accountability and corporate responsibility. The research method was based on systematic bibliographical research, through the search for journals and international acts, in addition to the review of classic authors of Business Law, Constitutional Law and Human Rights. In addition, research searches were also conducted on Transparency International data, such as the 2021 Corruption Perceptions Index and Transparency and Public Governance Index. Keywords such as advance directives of Public Compliance, corporate governance, collective rights, corruption, among others.Keywords: Public compliance; corporate governance; public integrity; collective rights; corruption.